Outcomes of Different Health Care Contexts for Direct Transport to a Trauma Center versus Initial Secondary Center Care: A Systematic Review and Meta-analysis. (1st October 2013) - Williams, Teresa; Finn, Judith; Fatovich, Daniel; Jacobs, Ian
Abstract: Introduction . Within a trauma system, pre-hospital care is the first step in managing the trauma patient. Timely and appropriate transport of the injured patient to the most appropriate facility is important. Many trauma systems mandate that serious trauma cases are transported directly to a level I trauma center unless transfer to a closer hospital is deemed necessary to resuscitate and stabilize the patient prior to onward transfer to definitive care. Statistical and clinical heterogeneity is often high and is likely to be influenced by the heath care context.Methods . We conducted a systematic review and meta-analysis to compare patient outcomes for patients with serious trauma transported directly to a Level I/II trauma center ('direct' group) to those transported to a healthcare facility before transfer to the Level I/ II trauma center ('transfer' group). A search of bibliographic databases and secondary sources that focus on trauma was made. Studies were grouped by region: United States of America, Canada, Europe, Asia, Australia and New Zealand and South Africa.Results . The review included 43, 554 patients from the 30 studies that met the selection criteria. Heterogeneity of the studies was high (I 2 71%) overall but low for European, Asian, and Australian and New Zealand studies. There was considerable variation between studies in the structure, policies and practices of the respective trauma systems. The effect of "directness" on patient outcomes was inconsistent. Conclusion. The current research evidence does not support nor refute a position that all serious trauma patients be routinely transported directly to a level I/II trauma center. As this is a complex issue, local health-care context and injury profile influence trauma policy and practice.Key words: trauma; trauma center; emergency medical services; transport